Pengaruh Harga, Kualitas Produk Dan Citra Merek Terhadap Keputusan Pembelian Pada Produk Citra Handbody Lotion (Studi Kasus Pada Mahasiswa Universitas Muhammadiyah Surakarta) - Andini, Dhita Budi; , Ma'ruf, Drs., MM (2017)
This study aims to determine the effect of price, product quality and brand image to the purchasing decisions of product citra handbody lotion. The sample in this study is a student at the University of Muhammadiyah Surakarta that use imagery products handbody lotion with questionnaires of 100 respondents. Techniques in this study were taken by convenience sampling. Data analysis method used is the validity, reliability, and test multiple linear regression analysis with t-test, F and coefficient of determination (R2). Hypothesis tests showed price, product quality and brand image have significant influence with t respectively -2.066, 2.190, and 5.165. In the F test showed that together the variable price, product quality and brand image significantly influence purchasing decisions with a probability value of 0.000 (0.000 <0.05). And the coefficient of determination (R2) of 32.6%.